Differences in Behavior and Brain Activity during Hypothetical and Real Choices. Issue 1 (January 2017) - Camerer, Colin; Mobbs, Dean
Abstract : Real behaviors are binding consequential commitments to a course of action, such as harming another person, buying an Apple watch, or fleeing from danger. Cognitive scientists are generally interested in the psychological and neural processes that cause such real behavior. However, for practical reasons, many scientific studies measure behavior using only hypothetical or imagined stimuli. Generalizing from such studies to real behavior implicitly assumes that the processes underlying the two types of behavior are similar. We review evidence of similarity and differences in hypothetical and real mental processes. In many cases, hypothetical choice tasks give an incomplete picture of brain circuitry that is active during real choice. Trends: Many experiments in cognitive neuroscience use hypothetical choices, or use stimuli that lack some realistic features. The goal of the experiments, however, is to understand behavior and brain activity during real choices people make. Hypothetical and limited-realism experiments run the risk of understating the strength of brain activities, or giving an incomplete picture of the neural mechanisms, which are evoked by real choices. There is some evidence of differences in behavior and brain activity between hypothetical and real choice in domains of social, moral, and economic choice. There are also differences in brain activity, between more or less realistic stimuli, in emotional reactions and in visual processing. More studies directly comparing hypothetical and real choice are needed, as well as imaginative realistic paradigms.